Presence of extended-spectrum β-lactamase in Escherichia coli strains isolated from beef, pork, and chicken meats sold in Recife, Brazil - SILVA, Órion Pedro da; LEITE, Denny Parente de Sá Barreto Maia; BARBOSA, Iago Carvalho; SILVA, Michelle Machado de Oliveira; SILVA, Alane Pereira da; MOREIRA, Maria Aparecida Scatamburlo; MOURA , Andrea Paiva Botelho Lapenda de; BARROS, Mércia Rodrigues; MOTA, Rinaldo Aparecido (Food Science and Technology, 2025)
This study aimed to identify extended-spectrum β-lactamase (ESBL)-producing Escherichia coli in chicken, beef, and pork meats sold in Recife, Pernambuco, Brazil. A total of 120 meat samples (40 of each type) were collected from supermarkets, butcher shops, and open-air markets across the city’s eight health districts, using convenience sampling. The samples were processed in a microbiology laboratory, and E. coli was identified through selective isolation on eosin-methylene blue agar and biochemical tests. Phenotypic resistance was assessed using disk diffusion tests on Müller–Hinton agar with cefotaxime, ceftazidime, and ceftriaxone disks, followed by the double-disk synergy test to confirm ESBL production. Genotypic analysis was conducted by polymerase chain reaction to detect the blaTEM and blaSHV genes. Of the 40 E. coli isolates obtained, 34 (85%) exhibited phenotypic resistance, while 21 (52.5%) and 23 (57.5%) tested positive for the blaSHV and blaTEM genes, respectively. A higher prevalence of blaSHV was observed in pork samples (73.3%, 11/15), whereas blaTEM was more prevalent in beef (70%, 7/10). The presence of resistant bacteria in commercial meats highlights contamination risks in the production chain and underscores the need for surveillance and public awareness to protect human health.